Teknik Komunikasi Persuasif Buya Yahya Pada Ceramah “Apa Dan Bagaimana Hijrah Itu?” - Kelaut Dia; Sri Wahyuni (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2021)
KH. Yahya Zainul Ma'arif (Buya Yahya) in the lecture "What and How Is Hijrah?", There is a persuasive communication technique, because there are many positive responses from mad'u. The existence of positive audience participation on the message conveyed, indicates the successful application of persuasive communication techniques. This study explains Buya Yahya's persuasive communication technique in the lecture "What and How Is Hijrah?". The study methodology is a qualitative researcher with the Philipp Mayring content analysis method, namely the research used to examine the content of messages in a communication process, in this study the content of da'wah messages. This study used video transcribed into text, then analyzed using a coding agenda with the patterns and categories of each persuasive communication technique used in this study. The data were collected through observation of broadcasts on the Al-Bahjah TV Youtube channel in the video lecture entitled "What and How Is Hijrah?". As a result, there are seven persuasive communication techniques used by Buya Yahya in his lecture "What and How Is Hijrah?" namely: association technique, integration technique, reward technique or “pay-off” technique, “Putting it up to you” technique, transfer technique, “bandwagon” technique, “don't ask if” technique and “ask which” technique. With the persuasive communication techniques used by preachers in conveying their da'wah messages, hopefully that mad'u can easily understand, so the purpose of da'wah communication is easily achieved.